2017
DOI: 10.1182/blood-2017-06-793141
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and biomarkers of severe cytokine release syndrome after CD19 chimeric antigen receptor–modified T-cell therapy

Abstract: Lymphodepletion chemotherapy followed by infusion of CD19-specific chimeric antigen receptor-modified (CAR) T cells has produced impressive antitumor responses in patients with refractory CD19 B-cell malignancies but is often associated with cytokine release syndrome (CRS). Our understanding of CRS continues to evolve, and identification of the kinetics of CRS and predictive clinical and laboratory biomarkers of severity are needed to evaluate strategies to mitigate toxicity. We report the clinical presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
956
4
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 875 publications
(1,001 citation statements)
references
References 33 publications
26
956
4
15
Order By: Relevance
“…This precautionary approach was required in the clinical trials of axi-cel, but we have not found this to be necessary in studies using CAR T cell constructs containing a 4-1BB co-stimulatory domain, including tisagenlecleucel, JCAR014, and JCAR017, in both ALL and NHL populations. Fever is typically the presenting symptom of CAR T cell-associated CRS (at least with 4-1BB CAR T cells), with critical illness arising 12-96 h later, if at all [7][8][9][10][11][12] . Patients can therefore be infused with CAR T cells in the outpatient setting and admitted to hospital at the time of fever development.…”
mentioning
confidence: 99%
“…This precautionary approach was required in the clinical trials of axi-cel, but we have not found this to be necessary in studies using CAR T cell constructs containing a 4-1BB co-stimulatory domain, including tisagenlecleucel, JCAR014, and JCAR017, in both ALL and NHL populations. Fever is typically the presenting symptom of CAR T cell-associated CRS (at least with 4-1BB CAR T cells), with critical illness arising 12-96 h later, if at all [7][8][9][10][11][12] . Patients can therefore be infused with CAR T cells in the outpatient setting and admitted to hospital at the time of fever development.…”
mentioning
confidence: 99%
“…The mechanism for neurotoxicity is not clearly understood, but in view of the correlation between severity of CRS and of CRES, the latter does appear to be related to systemic inflammation in the setting of rapid early CAR T cell expansion, and particularly with the rapid upstroke of systemic inflammatory cytokines such as IL-6 38 . This has led to the implication of rapid transfer of inflammatory cytokines from the systemic circulation into the CSF as a potential mechanism.…”
Section: Car T Cell-related Encephalopathy Syndrome (Cres)mentioning
confidence: 93%
“…Investigation of biomarkers of severe CRS in a predominantly paediatric cohort revealed an association between low fibrinogen and grade 4 CRS in paediatric patients 35 . This was explored further in an adult cohort treated at the Fred Hutchinson Cancer Center 38,45 where grade 4 or greater CRS was associated with hypofibrinogenaemia, increased d-dimers and reduced platelets, consistent with disseminated intravascular coagulation.…”
Section: Cytokine Release Syndrome (Crs)mentioning
confidence: 98%
See 2 more Smart Citations